2020
DOI: 10.1038/s41598-020-76616-y
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of macrocrack location in concrete, rocks and other granular composite materials

Abstract: Heterogeneous quasibrittle composites like concrete, ceramics and rocks comprise grains held together by bonds. The question on whether or not the path of the crack that leads to failure can be predicted from known microstructural features, viz. bond connectivity, size, fracture surface energy and strength, remains open. Many fracture criteria exist. The most widely used are based on a postulated stress and/or energy extremal. Since force and energy share common transmission paths, their flow bottleneck may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Interestingly, Li and co-workers also observed particle clusters in the mesoregime of gas/solid-particle flow systems, and conjectured that these emerge from particles tending to minimize their potential energy, while the gas tries to choose a path of least resistance through the particle layers 29 – 31 . Analogously, in the systems studied here, damage favors the path of least resistance to failure – the path that forms the common boundaries of kinematic clusters 13 , 14 .…”
Section: Precursory Dynamics Of Granular Failure Across System Levels and Scalesmentioning
confidence: 83%
See 4 more Smart Citations
“…Interestingly, Li and co-workers also observed particle clusters in the mesoregime of gas/solid-particle flow systems, and conjectured that these emerge from particles tending to minimize their potential energy, while the gas tries to choose a path of least resistance through the particle layers 29 – 31 . Analogously, in the systems studied here, damage favors the path of least resistance to failure – the path that forms the common boundaries of kinematic clusters 13 , 14 .…”
Section: Precursory Dynamics Of Granular Failure Across System Levels and Scalesmentioning
confidence: 83%
“…Some are preferred over others. Experimental studies into the transmission of force and energy in natural and synthetic granular media (e.g., sand, photoelastic disk assemblies) and associated discrete element simulations have shown that the mesoregime of PFR is governed by the coupled evolution of two dominant mechanisms 13 15 , 32 , 33 . The first comprises the preferred paths for force transmission (mechanism A): a set of system-spanning paths that can transmit the highest force flow along direct and shortest possible routes through the system.…”
Section: Precursory Dynamics Of Granular Failure Across System Levels and Scalesmentioning
confidence: 99%
See 3 more Smart Citations